2-((E)-1-((E)-(2-methoxybenzylidene)hydrazono)ethyl)phenol based cost-effective sensor for the selective detection of Eu3+ ions. (15th November 2021) - Virender,; Mohan, Brij; Kumar, Sandeep; Modi, Krunal; Deshmukh, Abdul Hakeem; Kumar, Ashwani
Graphical abstract: The presence of imine functionalities and –OH group in the ligand 2-((E)-1-((E)-(2-methoxybenzylidene)hydrazono) ethyl)phenol (MHEP)lead to a highly selective sensor for Eu 3+ ions among various metal ions. The UV–visible, fluorescence and electrochemical studies reveal sensing behavior of NHEP for Eu 3+ ions. The UV–visible titrations are used to determine the limit of detection 1.2 × 10 −7 M, the limit of quantitation 41 × 10 −7 M and linear range 22 × 10 −6 M −1 to 124 × 10 −6 M −1 are determined. Abstract: The detection of lanthanides has emerged as an attractive field of research due to potential applications in biomedical sciences. Here we design a simple and cost-effective ligand 2-((E)-1-((E)-(2-methoxybenzylidene)hydrazono)ethyl)phenol (MHEP ) that acts as a rapid selective sensor for Eu 3+ ions with a blue shift in UV–visible, ratiometric enhancement in fluorescence intensity and significant redox potential changes in cyclic voltammetric graph among various metal ions in the CH3 OH:H2 O (1:1, v/v) solvent system. The UV–visible titrations are used to determine the limit of detection 1.2 × 10 −7 M, the limit of quantitation 41 × 10 −7 M and linear range 22 × 10 −6 M −1 to 124 × 10 −6 M −1 are determined. The binding stoichiometry is determined by Job's plot, mole ratio method and Benesi-Hildebrand plot that is found 1:1 (MHEP:Eu 3+ ) with association constant 2.360 × 10 5 M −1 . The IR spectroscopy reveals the role of imine functionalities for the Eu 3+ ions detection.